2021
DOI: 10.1158/1535-7163.targ-21-p233
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P233: TAS0953/HM06 is effective in preclinical models of diverse tumor types driven by RET alterations

Abstract: Fusions involving RET receptor tyrosine kinase are a common driver of tumors across different tissue types, such as lung, thyroid, colorectal, soft tissue and others. TAS0953/HM06 (hereby referred to as HM06) is a novel 2ndgeneration RET-specific inhibitor that is effective against RET solvent front (G810) and gatekeeper (V804) mutations. Here, we evaluated the efficacy of HM06 in lung and thyroid carcinomas, and soft-tissue sarcoma cell lines and PDXs derived from RET inhibitor-naive tumor samples or from tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…While Pralsetinib and Selpercatinib are able to overcome bulky GK mutations but are vulnerable to SF mutations, TPX-0046 might show the opposite activity spectrum being able to overcome SF mutations, but remaining vulnerable to GK mutations. Meanwhile GK and SF tolerant RET inhibitors have currently entered Phase-I clinical trials (TAS0953) [17].…”
Section: Discussionmentioning
confidence: 99%
“…While Pralsetinib and Selpercatinib are able to overcome bulky GK mutations but are vulnerable to SF mutations, TPX-0046 might show the opposite activity spectrum being able to overcome SF mutations, but remaining vulnerable to GK mutations. Meanwhile GK and SF tolerant RET inhibitors have currently entered Phase-I clinical trials (TAS0953) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Vepafestinib inhibited the growth of multiple lung cancer patient-derived cell lines harboring RET fusions with different N-terminal partners ( CCDC6 , KIF5B , TRIM33 ) and an RET C634W mutation–positive MTC cell line and was active in a number of NSCLC xenograft models. Preclinical models suggested that vepafestinib penetrates the CNS more than selpercatinib and is superior in decreasing CNS disease and extending survival in mice [ 41 , 42 ]. Vepafestinib is currently undergoing a biomarker-driven phase I/II clinical trial (MARGARET) in the US and Japan for patients with solid tumors driven by RET alterations that have progressed on existing therapies (NCT04683250, accessed 3 November 2023).…”
Section: Next-generation Selective Ret Inhibitors In Clinical Develop...mentioning
confidence: 99%
“…While TPX-0046 cannot circumvent the V804 gatekeeper mutation, a Phase I/II clinical trial (NCT04161391) is ongoing in patients with advanced solid tumors harboring RET alterations. HM06, another investigational compound, selectively inhibits RET across multiple tumor types in vitro and in vivo , circumvents RET-V804X gatekeeper mutation and RET-G810X resistance mutations ( 284 , 285 ), and is currently in Phase I/II clinical trials in patients with RET-altered tumors (NCT04683250). Lastly, LOX-18228 is a novel compound that potently inhibits RET, RET fusions, and can even inhibit RET-V804X and RET-G810X mutations singly or in tandem ( 286 ), suggesting that LOX-18228 may be effective in targeting tumors with resistance to first-generation RET inhibitors.…”
Section: Resistance To First-generation Ret Inhibitors and Developmen...mentioning
confidence: 99%